Oil extracts of wild apple fruit as source of bioactive substances in cosmetic products for skin hydration - Stojiljković, Dragana; Nešić, Ivana; Tadić, Vanja (Archives of Pharmacy, 2022)
Wild apple fruit represents a good source of bioactive hydrating substances (polyphenols-PP and fruit acids-FA). Application of cosmetic products with oil extracts of wild apple fruit might show favorable hydrating effects. The aim of study was the preparation of oil extracts of wild apple fruit (Malus sylvestris fructus (L.) Mill., Rosaceae), originated from Serbia, preparation of cosmetic cream with oil extract, investigation of PP and FA content, and in vivo investigation of efficacy of cream containing oil extract after skin application. Liquid oil extracts were prepared in the drug:extract ratio 1:5 (m:m) with sunflower oil as solvent and maceration-EM and digestion-ED as extraction methods, while ED was incorporated into the cream o/w type, stabilized by biodegradable mixed emulsifiers. Content of PP and FA was determined by HPLC analysis. In vivo efficacy included investigation of skin hydration potential of the cream, transepidermal water loss-TEWL and skin pH after 14 and 28 days of cream application on healthy volunteers’ skin. Content of identified bioactive substances was better in extract EM (PP content: 7000.71mg/100gED and 27.14mg/100gEM and FA content: 2618.76mg/100gED and 281.25mg/100gEM). In vivo study revealed an increase of skin hydration (ΔEC was 14.98 ± 6.58 after 14 days and 10.12 ± 5.86 after 28 days), with unchanged TEWL and skin pH values. Obtained results indicate that oil extracts of wild apple fruit represent a valuable source of bioactive substances with good hydrating effects of the cream on human skin, so it might potential used in cosmetic products for skin hydration.